Bibliometric analysis of the top-100 cited articles on oral potentially malignant disorders to guide research topic and direction - Liwei Ma; Xing Gao; Wei Liu (Elsevier, 2020)
Background/purpose: Bibliometric analysis highlights the key topics and studies which have shaped the understanding and management of a concerned disease. Here the top-cited articles on oral potentially malignant disorders (OPMD) were characterized and analyzed. Materials and methods: A comprehensive search was performed and identified in the Scopus database from 1941 to 10 March 2019 for the 100 most-cited articles on OPMD. Results: The number of citations of the 100 selected articles varied from 131 to 1422, with a mean of 240.6 citations per article. Molecular markers/targets, chemoprevention, and early detection and diagnosis of oral cancer were the top-3 study topics, and the proportion of the number of the articles on the top-3 topics and that of the number of citations was 47% and 47.7%, respectively. Moreover, 20 (90.9%) of the 22 high-quality articles published in journals with high IF > 9 were the research of top-3 topics. Besides, the most contributing author, Hong WK (n = 11), was from the most contributing institution and country of origin, M.D. Anderson Cancer Center (n = 12), United States (n = 41). Systematic reviews (n = 7), randomized controlled trial (n = 5), cohort studies (n = 18) were study designs with higher evidence level, but the large majority (n = 70) were considered lower level. Conclusion: The results of this first citation analysis of the 100 most-cited articles on OPMD provide a historical perspective and key topics, and suggest a troika for the trends of further research and clinical practice in the field of OPMD.